Endoscopic Hemostatic Treatment of Peptic Ulcer Bleeding - Yeon Hwa Choe; Jun Chul Park (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2018)
Peptic ulcer bleeding is a common complication of peptic ulcer disease and the most common cause of upper gastrointestinal bleeding. Despite advances in drug usage and endoscopic modalities, no significant improvement is observed in the mortality rate of bleeding ulcers. The purpose of this review is to discuss various endoscopic hemostatic methods to treat peptic ulcer bleeding. Endoscopic hemostatic techniques can be classified into injection, mechanical, electrocoagulation, hemostatic powder, and endoscopic Doppler-guided hemostatic therapies (the last mentioned being a newly developed technique). Endoscopic hemostasis can be performed as mono or combination therapy using the aforementioned methods. Endoscopic hemostasis is the most important treatment for patients with peptic ulcer bleeding. Endoscopists should consider the treatment approach for peptic ulcer bleeding based on patient characteristics, the size and shape of the lesion, the endoscopist’s expertise, and the resources and circumstances at each hospital. Follow-up studies are needed to evaluate the efficacy of newly developed hemostatic powder therapy and endoscopic Doppler-guided hemostasis.